Performance Comparison of Response Time Native, Mobile and Progressive Web Application Technology - Rochim, Rachma Verina; Rahmatulloh, Alam; El-Akbar, R Reza; Rizal, Randi (Department of Informatics, Siliwangi University, Indonesia, 2023)
The development of technology in web-based applications is growing, this creates new problems. The web technology that is currently being discussed is Progressive Web Application (PWA) but is the PWA's performance better than the previous technology. This research is about measuring the performance of the Native Web, Mobile Web and PWA using three testing tools, namely GTMetrix, Lighthouse, and Chrome DevTool. The results of this study show how to measure the performance of a Progressive Web Application (PWA), where PWA can beat the performance of Native Web and Mobile Web if a web page is tested more than once. Test results on the Progressive Web Application (PWA), the minimum number of page files (home) is 217 kB with page loading time of 638 ms, while the medium page (about) is 431 kB with page loading time of 646 ms, and when accessing heavy pages (news) with a size of 41700 kB the page load time is 532 ms.